Informed consent for functional MRI research on comatose patients following severe brain injury: balancing the social benefits of research against patient autonomy. Issue 5 (25th February 2019) - Bruni, Tommaso; Graham, Mackenzie; Norton, Loretta; Gofton, Teneille; Owen, Adrian M; Weijer, Charles
Abstract : Functional MRI shows promise as a candidate prognostication method in acutely comatose patients following severe brain injury. However, further research is needed before this technique becomes appropriate for clinical practice. Drawing on a clinical case, we investigate the process of obtaining informed consent for this kind of research and identify four ethical issues. After describing each issue, we propose potential solutions which would make a patient's participation in research compatible with her rights and interests. First, we defend the need for traditional proxy consent against two alternative approaches. Second, we examine the impact of the intensive care unit environment on the informed consent process. Third, we discuss the therapeutic misconception and its potential influence on informed consent. Finally, we deal with issues of timing in recruiting participants and related factors which may affect the risks of participation.